Building an Efficient Component for OCL Evaluation - Clavel, Manuel; Marina, Egea; Miguel Angel, Garcia de Dios (Electronic Communications of the EASST, 2008)
In this paper we report on our experience developing the Eye OCLSoftware (EOS) evaluator, a Java component for efficient OCL evaluation. We firstmotivate the need for an efficient implementation of OCL in order to cope with novelusages of the language. We then discuss some aspects that, based on our experience,should be taken into account when building an OCL evaluator for medium-largescenarios. Finally, we explore various approaches for evaluating OCL expressionson really large scenarios.